Law and the "Sharing Economy": Regulating online market platforms - Derek McKee; Finn Makela; Teresa Scassa (University of Ottawa Press, 2018)
The rapid expansion of sharing economy platforms has generated enormous controversy. Law and the "Sharing Economy" closely examines the challenges that arise from this phenomenon with regard to labour, market, technology and regulation through a legal and interdisciplinary lens. The controversy stems partially from the economic impact - most acutely in certain sectors such as Uber vs taxi drivers and Airbnb vs hotels - and partially from other related consequences such as a trend toward precarious work or an impact on real estate speculation. While governments in some jurisdictions have attempted to rein in the platforms, technology has enabled such companies to bypass conventional regulatory categories, generating accusations of "unfair competition" as well as debates about the merits of existing regulatory regimes.
hdl:10393/38506
Keywords: 330; Sharing economy; Platform economy; Regulation; Labour law; Technology law